Nanoparticle-Based Dressing: The Future of Wound Treatment?. Issue 8 (August 2017) - Berthet, Morgane; Gauthier, Yves; Lacroix, Céline; Verrier, Bernard; Monge, Claire
Abstract : Reconstructing functional skin after a wound remains a challenge due to the complexity of healing. In this regard, biocompatible nanoparticles (NPs) carrying and releasing bioactive drugs in a controlled and sustained manner may significantly improve the efficacy of wound therapies compared with current treatments. Topical administration of drug-loaded NPs allows optimal delivery to the dermis and improves product efficacy. Furthermore, associating NPs with scaffolds represents a new concept of 'dressing'. Experimental in vivo, ex vivo, and in vitro models have been developed in preclinical assays to evaluate the beneficial effects of nanoparticulate dressings. Drug-loaded NPs are promising tools for innovative wound healing treatment, especially with regard to their multifunctional properties. Trends: Nanoparticles (NPs) loaded with drugs such as growth factors or nucleic acids are promising tools for skin regeneration and represent a strategy for wound repair. Their incorporation into an 'intelligent' matrix to design a nanocomposite (NCP) gives rise to innovative dressings. Significant efforts are made to develop 'green processes' aimed at producing biocompatible composites. A successful outcome of these NCPs would result in a sequential release of loaded drugs following the healing process stages. Recent advances in alternative models to animal experimentation focus on in vitro human reconstructed skin cultured in static conditions. In vitro organ-on-a-chip techniques will allow the integration of microfluidic networks with 3D tissue-engineered models. This research field opens new windows for preclinical NP screening.